Reconstruction of Constitutional AI Electoral Governance for Election Legitimacy: A Comparison of Indonesia, the United States, and Singapore - Amirullah Amirullah; Sri Rahayu (Journal of Creative Power and Ambition (JCPA), 2026)
The development of Artificial Intelligence (AI) has changed the face of contemporary political campaigns, from just a communication support tool to an algorithmic power that influences the formation of voters' political preferences through micro-targeting, message personalization, and the production of synthetic content such as deepfakes. In Indonesia, this transformation has not been matched by the readiness of national law. Law Number 7 of 2017 concerning General Elections, the Personal Data Protection Law, and the Law on Information and Electronic Transactions are still sectoral and oriented towards enforcement after violations occur, so they have not been able to anticipate the characteristics of Generative AI, algorithmic political advertising, and synthetic media. This study aims to analyze the constitutional implications of the use of AI in political campaigns on the legitimacy of elections in Indonesia, compare its arrangements in the United States and Singapore, and formulate an appropriate regulatory model for Indonesia. The research uses normative legal methods that are prescriptive, with legislative, conceptual, comparative, and case approaches, which are analyzed qualitatively through systematic interpretation and legal reasoning. The results show that the use of AI has the potential to distort people's sovereignty, the right to correct information, and the principles of fair and fair elections, while the United States and Singapore each pursue complementary rights-based and risk-based governance approaches. Based on these findings, this study offers a novelty in the form of a Constitutional AI Electoral Governance (CAEG) model that builds five constitutional pillars to place AI as an object of constitutional law governance. The implications of the policy lead to the need to revise the Election Law and strengthen the adaptive authority of the KPU and Bawaslu in supervising the use of AI in political campaigns.